Strategi Pengembangan Jiwa Islamic Entrepreneurship di Era Society 5.0 - Ainun Rohmah; Mustofa (CV. ITTC INDONESIA, 2025)
The development of Entrepreneurship in the digital era provides significant opportunities to improve societal welfare; however, many business practices still fail to comply with Sharia principles. This study aims to analyze strategies for developing the spirit of Islamic entrepreneurship in the Society 5.0 era and to identify the integration of Islamic values with digital technology. The research applies a qualitative approach through literature review. The findings indicate that strengthening Islamic entrepreneurship can be achieved by emulating the Prophet Muhammad’s characteristics, fostering a positive entrepreneurial mindset, and regarding business activities as a form of worship. Strategies in the Society 5.0 era emphasize the utilization of digital technology supported by market awareness, social competence, quality orientation, collaboration, income diversification, and the application of sustainability principles. The results highlight that entrepreneurial success in this era is not solely determined by technological mastery but also by the moral, ethical, and spiritual foundations of Islam.